The Dynamics of Interpersonal Space in Congregational Prayers in Salman Mosque Bandung During Covid Pancemic - Aldyfra Luhulima Lukman; Indri Astrina Wirakusumah; Sahid Sahid; Edward Vinsensius Gunawan (Journal of Islamic Architecture, 2023)
The Covid-19 pandemic has caused drastic changes in everyday life in Indonesia, including Muslim religious activities facilitated by mosques. A mosque is intended to accommodate all worshipping activities that can provide benefits not only for congregants performing activities within, but also for communities and the environment around the mosque. One thing that remains constant in terms of the main functions of mosques is the accommodation of praying (salat) activities. In the times of Covid-19 pandemic, the implementation of rules concerning compulsory congregational prayers should be adjusted according to health protocols to minimize the spread of the coronavirus, especially the parts related to interpersonal space between individuals. This study intends to capture the dynamics of perception regarding interpersonal spaces according to congregants performing congregational prayers in the mosque. This study applies behavior mapping and questionnaire to collect data concerning the dynamics of perception regarding interpersonal spaces from Salman Mosque in Bandung. This study identifies the difference, in terms of congregational prayers, between how congregants perceive their interpersonal space differs from how they apply interpersonal distance. The difference is mostly influenced by self-interpretation concerning religious and/or government rules rather than total compliance to religious leaders and/or government instructions.